RASIONALITAS PENGGUNAAN ANTIPSIKOTIK PADA PASIEN GANGGUAN BIPOLAR DISORDER DI RSUD DR. LOEKMONO HADI KUDUS PERIODE JANUARI-JUNI 2024 - Nila Khumaela Sofwatussuba; Endang Setyowati; Emma Jayanti Besan (Yayasan Nusantara Hasana Berdikari, 2025)
Mental disorders around the world according to WHO (World Health Organization) data have the highest number of bipolar sufferers as many as 60 million people. The Indonesian Association of Psychiatric Specialists (PDSKJI) revealed that Bipolar disorder in Indonesia covers around 0.3% to 1.5%. Antipsychotics can have a major effect on overcoming manic episodes, preventing recurrence and treating major depressive disorders. The purpose of this study is to determine the rationality of the use of antipsychotics in bipolar disorder patients at dr. Loekmono Hadi Kudus Hospital. The data analysis method used a non-experimental design with retrospective descriptive analysis with research materials in the form of patient medical records. The results of data collection were 95 selected patients, the majority of bipolar patients were women (76.8%), vulnerable 25-34 years old (27.4%), high school education/equivalent (36.8%), had other jobs (33.7%), used BPJS payment type (96.8%), used single antipsychotic drugs (73.7%), antipsychotics that were often used were quetiapine (24.2%). The results of the evaluation were indicated, the patient was right, the drug was 100% right, and the dose was 98.9% right. The use of antipsychotic drugs in patients with bipolar disorder at dr. Loekmono Hadi Kudus Hospital for the period January – June 2024 can be said to be rational because it is in accordance with the pharmacotherapy handbook 9 th edition and the VA/DoD Clinical Practice Guideline for Management of Bipolar Disorder.